2010
DOI: 10.18388/abp.2010_2375
|View full text |Cite
|
Sign up to set email alerts
|

New method for the study of Amaryllidaceae alkaloid biosynthesis using biotransformation of deuterium-labeled precursor in tissue cultures.

Abstract: Biotransformation of deuterated-4'-O-methylnorbelladine into alkaloids galanthamine and lycorine in tissue cultures of Leucojum aestivum was demonstrated using HPLC coupled to mass spectrometry. GC-MS screening was also carried to investigate other native and deuterated alkaloids. A total of six labeled alkaloids were identified indicating that 4'-O-methyl-d(3)-norbelladine is incorporated into three different groups of Amaryllidaceae alkaloids that are biosynthesized by three modes of intramolecular oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…These results showed that only at 0.1 g/L, the precursor enhanced the galanthamine accumulation in the shoot cultures. This latter alkaloid was either partially released into the liquid medium or partially transformed in other compounds as shown in a previous study [20], where labeled narwedine and N-formylgalanthamine were found in the shoot cultures. In control shoot cultures, lycorine was detected in the tissues (0.04 mg/g DW) at a constant level throughout the whole culturing period.…”
Section: Resultssupporting
confidence: 68%
“…These results showed that only at 0.1 g/L, the precursor enhanced the galanthamine accumulation in the shoot cultures. This latter alkaloid was either partially released into the liquid medium or partially transformed in other compounds as shown in a previous study [20], where labeled narwedine and N-formylgalanthamine were found in the shoot cultures. In control shoot cultures, lycorine was detected in the tissues (0.04 mg/g DW) at a constant level throughout the whole culturing period.…”
Section: Resultssupporting
confidence: 68%
“…Control medium free of MN was also used. The cultures were in-cubated for various periods of time (15,30,40 and 50 days) under white fluorescent light with a 16 h photoperiod (Tungsram lamp, 40 WF, 90 μmol m −2 s −1 ) at 25 ± 2°C. Three replicates for each condition were made.…”
Section: Bulblet Culturesmentioning
confidence: 99%
“…In a previous work [30], deuterated MN was prepared according to a method reported by Szewczyk et al [42] to synthesize the undeuterated precursor. It involved a reductive amination of isovanillin with tyramine.…”
Section: Optimization Of 4'-o-methylnorbelladine (Mn) Synthesismentioning
confidence: 99%
“…24,[30][31][32]36 In vitro studies in such settings have shown that lycorine can induce apoptosis, specifically targeted against malignant cells. 31 Its potential use as a therapeutic agent has recently led to studies into the production of the synthetic compound, 40,41 highlighting it as a potential lead for drug development. 24,42 In this study we investigated the potential of combining lycorine with bezafibrate + MPA to elicit an apoptotic response in the presence of CD40L and assessed the correlation between induced apoptosis and the generation of mitochondrial superoxide.…”
Section: Introductionmentioning
confidence: 99%